2009
DOI: 10.1038/onc.2009.58
|View full text |Cite
|
Sign up to set email alerts
|

Human FEM1B is required for Rad9 recruitment and CHK1 activation in response to replication stress

Abstract: Human checkpoint kinase 1 (CHK1) is an essential kinase required to preserve genome stability, and is activated by DNA replication blockage through the ataxia-telangiectasia-mutated-and-Rad3-related (ATR)/ATRIP-signaling pathway. In this report, we show that a novel CHK1-interacting protein, FEM1B (human homologue of the Caenorhabditis elegans sex determination fem1 protein), identified by a yeast two-hybrid screen, is involved in the activation of CHK1 by replication stress. Depletion of FEM1B by small interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…As for EHEC EspO1-1 we discovered another interaction with fem-1 homolog b (Fem1b), a component of an E3 ubiquitin-protein ligase complex acting as substrate recognition subunit 50 . Fem1b interacts with the checkpoint kinase CHEK1 to sense replication stress 51 and can act as a proapoptotic protein in cancer cells 52 53 54 . EHEC EspO1-1 may be another candidate that could act anti-apoptotically through its Fem1b interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As for EHEC EspO1-1 we discovered another interaction with fem-1 homolog b (Fem1b), a component of an E3 ubiquitin-protein ligase complex acting as substrate recognition subunit 50 . Fem1b interacts with the checkpoint kinase CHEK1 to sense replication stress 51 and can act as a proapoptotic protein in cancer cells 52 53 54 . EHEC EspO1-1 may be another candidate that could act anti-apoptotically through its Fem1b interaction.…”
Section: Resultsmentioning
confidence: 99%
“…SLC38A2 functions as a sodium-dependent amino acid transporter that mediates both the efflux of neutral α-amino acids across the blood-brain barrier and their uptake into neurons [67][68][69] . FEM1B is an ankyrin repeat protein that induces replication stress signaling through its interaction with checkpoint kinase 1 70 , regulates ubiquitin-protein transferase activity 71 and promotes apoptosis 72 . PYDC1 (also known as ASC2/POP1) regulates the innate immune response by suppressing NFκB transcription factor activity and pro-caspase-1 activation 73 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, FEM1B (Fem1 homolog B, MIM 613539) is a CRL2 substrate recognition subunit with a VHL-box for assembly with the other components of the E3 complex: Elongin C ( ELOC , MIM 600788) and Cullin 2 ( CUL2 , MIM 603135) 4 . FEM1B is a ubiquitous protein, localizing mainly in the cytoplasm, but studies based on cellular fractionation have also suggested a role in the nucleus 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Several functions of FEM1B include roles in apoptosis 6 , 7 , glucose homeostasis 8 , secondary sexual development 9 , replication stress pathways 5 , and more recently reductive stress pathways 10 , 11 . Although few FEM1B-substrate interactions have been resolved at the molecular level, FEM1B has been shown to interact with distinct types of amino-acid sequences, termed degrons.…”
Section: Introductionmentioning
confidence: 99%